PEMBERDAYAAN KELOMPOK WANITA TANI ARUM SARI MELALUI POTENSI LOKAL MENINGKATKAN EKONOMI KELUARGA DESA SEGOBANG KECAMATAN LICIN KABUPATEN BANYUWANGI - Balya Hidayat; Fitriatul Masruroh (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2021)
This study aims to empower women farmer groups Arum Sari through local potential in Segobang village, Licin sub-district, Banyuwangi district, starting with empowerment. In this case, the Arum Sari Women Farmer group in Segobang village takes advantage of the existing local potential to increase the family's economic income. The activities of the Arum Sari women farmer group are carried out once a week or once a month to hold group or community training that can attend the activity, usually attended by 30 members participating in the production of Karang Emas. The method used in this research is using a qualitative method. The research procedure that produces descriptive data is taking research subjects or informants in this study using purposive sampling. The aim of the researcher is to uncover the problems raised in the research. The training activity aims to improve the members of the women's farmer group Arum Sari. Empowerment carried out by the facilitator aims to increase the potential that exists in the area towards a better area. One of the efforts made to improve the family's economy is by utilizing local potential, namely sweet potatoes processed into Karang Mas